Designing and Developing A Teaching Scheduling Information System and A Mobile-Based Processing System: A Case Study in SMK Negeri 1 Tulang Bawang Tengah - Genis Priyantoro; Rangga Firdaus; Doni Andra; Hery Dian Septama (Journal of Sustainability Science and Technology, 2022)
The teaching scheduling system and value data processing used up to this point at SMK 1 Tulang Bawang Tengah are still not IT-based, which causes numerous errors, including schedules, changes to schedules that are inaccurate in real time, and the lengthy process of entering schedules, making it very difficult for staff. The schedule needs to be adequately organised, so we need an innovative method. The research that resulted in the development of this system was conducted using the waterfall methodology. The learning scheduling application and value data processing at SMK Negeri 1 Tulang Bawang Tengah were designed and developed utilising the waterfall technique, comprising four stages: analysis, design, coding, and testing. The results of black box testing applied to application testing show that the design matches expectations.